Endosymbiont-containing germarium transcriptional survey in a cereal weevil depicts downregulation of immune effectors at the onset of sexual maturity - Ferrarini, Mariana Galvão; Vallier, Agnès; Dell’Aglio, Elisa; Balmand, Séverine; Vincent-Monégat, Carole; Debbache, Mériem; Maire, Justin; Parisot, Nicolas; Zaidman-Rémy, Anna; Heddi, Abdelaziz; Rebollo, Rita (Frontiers in Physiology, 2023)
Insects often establish long-term relationships with intracellular symbiotic bacteria, i.e. endosymbionts, that provide them with essential nutrients such as amino acids and vitamins. Endosymbionts are typically confined within specialized host cells called bacteriocytes that may form an organ, the bacteriome. Compartmentalization within host cells is paramount for protecting the endosymbionts and also avoiding chronic activation of the host immune system. In the cereal weevil Sitophilus oryzae, bacteriomes are present as a single organ at the larval foregut-midgut junction, and in adults, at the apex of midgut mesenteric caeca and at the apex of the four ovarioles. While the adult midgut endosymbionts experience a drastic proliferation during early adulthood followed by complete elimination through apoptosis and autophagy, ovarian endosymbionts are maintained throughout the weevil lifetime by unknown mechanisms. Bacteria present in ovarian bacteriomes are thought to be involved in the maternal transmission of endosymbionts through infection of the female germline, but the exact mode of transmission is not fully understood. Here, we show that endosymbionts are able to colonize the germarium in one-week-old females, pinpointing a potential infection route of oocytes. To identify potential immune regulators of ovarian endosymbionts, we have analyzed the transcriptomes of the ovarian bacteriomes through young adult development, from one-day-old adults to sexually mature ones. In contrast with midgut bacteriomes, immune effectors are downregulated in ovarian bacteriomes at the onset of sexual maturation. We hypothesize that relaxation of endosymbiont control by antimicrobial peptides might allow bacterial migration and potential oocyte infection, ensuring endosymbiont transmission.